WT1 PEPTIDE VACCINATION IN COMBINATION WITH IMATINIB THERAPY FOR A PATIENT WITH CML IN THE CHRONIC PHASE - Miwako Narita, Masayoshi Masuko, Tohri Kurasaki, Toshiki Kitajima, Shoko Takenouchi, Anri Saitoh, Norihiro Watanabe, Tatsuo Furukawa, Ken Toba, Ichiro Fuse, Yoshifusa Aizawa, Manabu Kawakami, Yoshihiro Oka, Haruo Sugiyama, Masuhiro Takahashi (International Journal of Medical Sciences, 2010)
Although tyrosine kinase inhibitors is effective for dramatically reducing CML cells, it might be difficult to eradicate completely the CML stem cells. We aimed to clarify the safety and effects of WT1 peptide vaccination in combination with imatinib therapy for a CML patient. A 51 year-old male with CML in CP, who showed a resistance against imatinib therapy for 2.5 years, began to be treated with 9mer modified-type WT1 peptides in combination with standard dose of imatinib. Although every 2-week-administration of WT1 peptides for 22 weeks did not show definite effects on the quantification of bcr-abl transcripts, by changing the administration from every 2 weeks to 4 weeks bcr-abl transcripts decreased remarkably. After 11 months of every 4-week-administration of the peptides and 12 months post cessation of the peptides bcr-abl transcripts achieved to the level below detection by RQ/RT-PCR (complete molecular response). WT1/MHC tetramer+CD8+ CTLs, which appeared after the second administration of WT1 peptides and remained more than 15 in number among 106 CD8+ T cells throughout the administration of WT1 peptides, are still present in the blood on 14th month post cessation of the peptides. An in vitro study as to the cytotoxicity of lymphocytes induced by mixed lymphocyte peptide culture demonstrated that cultured lymphocytes possessed cytotoxicity against WT1 expressing leukemia cells and the cytotoxicity was WT1-specific and MHC class I restricted. The present study showed that WT1 peptide vaccination in combination with TKI is feasible and effective in the therapy for imatinib-resistant CML.